Pelatihan Pengembangan Usaha Kecil Bidang Pangan di Kumudasmoro Selatan, Semarang - Ch. Trihardjanti Nugrahaningsih; Agustine Eva Maria Soekesi (Universitas Katolik Soegijapranata, 2019)
Community service is carried out in South Kumudasmoro with kalayan who are businessmen of food stalls and fruit juice entrepreneurs. The purpose of service is to provide training on how to develop small businesses that are currently being carried out by means of improvements in the production process. This service area is a partner capable of developing a business in a better way because it produces more quality products (healthy, tasty and attractive). The method used is to provide training in understanding quality products and facilitating healthier production and marketing tools. The results of dedication show that understanding partners are shown by changes in how to produce and market